Treatment of patients with multifocal motor neuropathy with immunoglobulins in clinical practice: the SIGNS registry. (May 2016) - Stangel, Martin; Gold, Ralf; Pittrow, David; Baumann, Ulrich; Borte, Michael; Fasshauer, Maria; Hensel, Manfred; Huscher, Dörte; Reiser, Marcel; Sommer, Claudia
Objectives: The management of patients with multifocal motor neuropathy (MMN) under everyday clinical conditions has been insufficiently studied. We therefore collected comprehensive observational data on patients with MMN who received intravenous (IV) or subcutaneous (SC) immunoglobulins (IGs) as maintenance therapy. Methods: This was a prospective, noninterventional study (registry) in neurological centres (hospitals and offices) throughout Germany. Results: As of 1 December 2015, 80 patients with MMN were included (mean age 55.4 ± 9.8 years, 67% males, mean disease duration 10.7 ± 10.2 years). The affected limb regions were predominantly distal muscle groups of the upper extremities. On the inflammatory neuropathy cause and treatment (INCAT) scale, 94% of the patients had some disability in the arms and 61% in the legs. At inclusion, 98.8% received IVIG and 1.3% SCIG. Substantial variation was observed between IVIG treatment intervals (every 0.7 to 17.3 weeks) and dosage (0.2–2.1 g/kg body weight received during a single administration; mean monthly dosage, 0.9 g/kg body weight). However, the mean monthly dosage was steady over time. At 1-year follow up, improvement was seen in muscle strength, INCAT and quality of life (QoL) scores (SF-36 questionnaire). Conclusions: The management of patients with MMN in everyday clinical practice demonstrates a wide range of absolute dosages and treatment intervals of IG, supporting the recommended practice of determining treatment dose on an individual patient basis. The improvements in muscle strength and reduction in disability, accompanied by increased QoL, strengthen the case for use of IG as a maintenance treatment for MMN.